Photobiomodulation on Bax and Bcl-2 Proteins and SIRT1/PGC-1α Axis mRNA Expression Levels of Aging Rat Skeletal Muscle - Fang-Hui Li; Yan-Ying Liu; Fei Qin; Qing Luo; Hai-Ping Yang; Quan-Guang Zhang; Timon Cheng-Yi Liu (International Journal of Photoenergy)
Objective. This study aimed to analyze the effects of low level laser irradiation (LLLI) on Bax and IGF-1 and Bcl-2 protein contents and SIRT1/PGC-1α axis mRNA expression levels to prevent sarcopenia in aged rats. Material and Methods. Twenty female Sprague Dawley rats (18 months old) were randomly divided into two groups (n=10 per group): control (CON) and LLLI groups. The gallium-aluminum-arsenium (GaAlAs) laser irradiation at 810 nm was used in the single point contact mode (3.75 J/cm2; 0.4 cm2; 125 mW/cm2; 30 s). Bax, Bcl-2, and IGF-1 proteins and SIRT1/PGC-1α axis mRNA expression were assessed 24 h after LLLI on gastrocnemius in aged rat. Results. Gastrocnemius muscle weights, gastrocnemius mass/body mass, Bcl-2/BAX ratio, Bcl-2 protein, IGF-1 protein, and the mRNA contents in SIRT1, PGC-1α, NRF1, TMF, and SOD2 were significantly (P<0.05) increased by LLLI compared to CON group without LLLI. However, levels of BAX protein and caspase 3 mRNA were significantly attenuated by LLLI compared to CON group (P<0.05). Conclusion. LLLI at 810 nm inhibits sarcopenia associated with upregulation of Bcl-2/BAX ratio and IGF-1 and SIRT1/PGC-1α axis mRNA expression in aged rats. This indicates that LLLI has potential to decrease progression of myocyte apoptosis in sarcopenic muscles.